2016
DOI: 10.1007/s11442-016-1317-9
|View full text |Cite
|
Sign up to set email alerts
|

International progress and evaluation on interactive coupling effects between urbanization and the eco-environment

Abstract: Global urbanization is exerting severe stress and having far-reaching impacts on the eco-environment, and yet there exists a complex non-linear coupling relationship between the two. Research on the interactive coupling effect between urbanization and the eco-environment will be a popular area of study and frontier in international earth system science and sustainability science in the next 10 years, while also being a high-priority research topic of particular interest to international organizations. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(87 citation statements)
references
References 239 publications
(219 reference statements)
1
73
0
Order By: Relevance
“…Ambient (outdoor) air pollution usually refers to the phenomenon that due to human activities or natural processes, some substances enter the air and endanger the comfort, health, and welfare of the human body when they remain in the air at a high concentration for a long time [1,2]. With the continuous acceleration of the urbanization process, PM 2.5 has become one of the major pollutants of smog outbreaks [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Ambient (outdoor) air pollution usually refers to the phenomenon that due to human activities or natural processes, some substances enter the air and endanger the comfort, health, and welfare of the human body when they remain in the air at a high concentration for a long time [1,2]. With the continuous acceleration of the urbanization process, PM 2.5 has become one of the major pollutants of smog outbreaks [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, various environmental pollution and serious destruction of resources often occur in or around cities with concentrated population [4]. This may be the stress effect of urbanization on the ecological environment as demonstrated by many previous studies [10,11]. With the increase of a terrain gradient, the ecosystem health condition gradually improved.…”
Section: Temporal-spatial Relationship Between Esh and Himentioning
confidence: 96%
“…Therefore, the research on urbanization and the ecological environment system has become a hot topic in the academic field. Fang et al [10] created the theoretical framework of the interaction coupling effect between urbanization and the ecological environment. Liu et al [11] revealed the stress effect of urbanization by human activities on the ecological environment and the constraint effect of the ecological environment on urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…[4]. The impact of human activities is mainly reflected through land use change [5]. Current changes in river runoff vary on different scales and the report of IPCC (Intergovernmental Panel on Climate Change) in 2013 predicted that global climate change is likely to exert substantial impacts on surface water resource across the world [6].…”
Section: Introductionmentioning
confidence: 99%